Wooden Stepping Stones: Diversity and Biogeography of Deep-Sea Wood Boring Xylophagaidae (Mollusca: Bivalvia) in the North-East Atlantic Ocean, With the Description of a New Genus - Romano, Chiara; Nunes-Jorge, Amandine; Le Bris, Nadine; Rouse, Greg W.; Martin, Daniel; Borowski, Christian (Frontiers in Marine Science, 2020)
Wood boring bivalves of the family Xylophagaidae inhabit sunken wood on the deep-sea floor where they play a key role in the degradation of this organic matter in the ocean. The patchiness of the wood-fall habitats is impeding targeted sampling and little is therefore known on xylophagaid biology. We investigated for the first time the diversity and biogeography of Xylophagaidae in the NE-Atlantic and the Mediterranean over a broad geographic range and in various water depths using experimental wood deployments. We combined morphological and molecular analyses for species discrimination. A phylogenetic reconstruction based on 18S and 28S rRNA and COI genes revealed paraphyly of the type genus Xylophaga Turton, 1822, and led us to revise taxonomy and erect the genus Xylonora gen. nov.. COI haplotypes of the most abundant species revealed broad Atlanto-Mediterranean genetic connectivity for Xylophaga dorsalis and Xylonora atlantica new comb., while genetic connectivity appears limited for Abditoconus brava across the entrance of the Mediterranean. We provide the first DNA barcode data for Xylophagaidae as a solid base for future taxonomic work. Wood deployments in a broad geographic range provided a powerful tool for research on Xylophagaidae allowing for conclusions on ecological requirements of xylophagaid species.